2005
DOI: 10.1200/jco.2005.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Role of Anti-Hepatitis C Virus (HCV) Treatment in HCV-Related, Low-Grade, B-Cell, Non-Hodgkin's Lymphoma: A Multicenter Italian Experience

Abstract: This experience strongly provides a role for antiviral treatment in patients affected by HCV-related, low-grade, B-cell NHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
159
1
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 237 publications
(176 citation statements)
references
References 35 publications
10
159
1
6
Order By: Relevance
“…Antiviral treatment (AT) has been shown to induce remission of MC-related clinical manifestations and to reduce their transformation to overt B-NHL [12]. In patients with low-grade HCV-related NHL, clearance of HCV infection can lead to regression of the tumour burden [13][14][15]. Moreover, there is a correlation between hematological and virologic responses in patients with MZL, constituting the strongest indicator linking HCV infection with lymphomagenesis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Antiviral treatment (AT) has been shown to induce remission of MC-related clinical manifestations and to reduce their transformation to overt B-NHL [12]. In patients with low-grade HCV-related NHL, clearance of HCV infection can lead to regression of the tumour burden [13][14][15]. Moreover, there is a correlation between hematological and virologic responses in patients with MZL, constituting the strongest indicator linking HCV infection with lymphomagenesis [13].…”
Section: Introductionmentioning
confidence: 99%
“…The low incidence of SMZL among the low grade B-cell lymphomas and leukemias has made it difficult to gather information on its pathogenesis. Although the etiology of SMZL is unknown, it has been suggested that, in some patients, a chronic persistent antigen stimulation by the hepatitis C virus [6][7][8], the malaria parasite [9], or even by an autoantigen or a hitherto unknown foreign antigen, is responsible for initiating and triggering the disease. This first step would initiate a polyclonal expansion of B cells in the marginal zone of the spleen, followed by second hits resulting in the deregulation of genes involved in lymphomagenesis, leading to the emergence of an independent clonal lymphoid proliferation and ending with For reprint orders, please contact reprints@expert-reviews.com the lymphoma.…”
Section: Epidemiology and Etiology Is Smzl Triggered By An Antigen?mentioning
confidence: 99%
“…Unfortunately, no data are available for the therapeutic management of lymphoma in patients with SS-HCV. In B cell lymphomas, diverse therapeutic options have been used, including conventional chemotherapy (31), monoclonal agents (41), antiviral (42) or antimicrobial agents (43), and, in some cases, no specific therapy (23). This heterogeneity in treating B cell lymphoma was also observed in our retrospective multicenter series of patients with SS-HCV, although etiopathogenically, 2 therapeutic options should be highlighted as future options.…”
Section: Discussionmentioning
confidence: 66%